MANAJEMEN RISIKO PADA PERUSAHAAN PENGIRIMAN BARANG (JNE) - Miskiyah, Zakiyatul; Widyaningsih, Bekti (ISTISMAR, 2022)
JNE is a company in the field of goods or package delivery service industry, which is often needed by the community, organizations or companies and the government because JNE is able to make deliveries quickly and efficiently. operational, market, environmental, liquidity, legal and so on. As for the risks experienced by JNE goods delivery companies, such as delays in the process of sending goods, lost or defective goods when they reach the recipient. The purpose of this discussion is to find out how the form of risk management is for the delivery of goods at JNE. This study uses library research methods.